2016
DOI: 10.3390/info7020035
|View full text |Cite
|
Sign up to set email alerts
|

User in the Loop: Adaptive Smart Homes Exploiting User Feedback—State of the Art and Future Directions

Abstract: Due to the decrease of sensor and actuator prices and their ease of installation, smart homes and smart environments are more and more exploited in automation and health applications. In these applications, activity recognition has an important place. This article presents a general architecture that is responsible for adapting automation for the different users of the smart home while recognizing their activities. For that, semi-supervised learning algorithms and Markov-based models are used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Analyzing the papers selected and summarized in Table S13, it can be observed that 78% of them exclusively analyze smart homes, 16% take into consideration smart buildings in general, 3% analyze both smart homes and buildings, while the remaining 3% of the selected papers refer to smart workplace environments. The authors of these scientific articles make use of different types of sensors in their analyses, including wireless sensor networks [70,115,[119][120][121][122][123][124]; passive infrared motion sensors [82,97,117,118,122,125,126]; motion sensors [25,70,81,118,120,127,128]; environmental sensors [10,25,81,82,[116][117][118]123,[127][128][129][130][131][132]; temperature sensors [116,118,120,123,125,[131][132][133]; humidity sensors…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Analyzing the papers selected and summarized in Table S13, it can be observed that 78% of them exclusively analyze smart homes, 16% take into consideration smart buildings in general, 3% analyze both smart homes and buildings, while the remaining 3% of the selected papers refer to smart workplace environments. The authors of these scientific articles make use of different types of sensors in their analyses, including wireless sensor networks [70,115,[119][120][121][122][123][124]; passive infrared motion sensors [82,97,117,118,122,125,126]; motion sensors [25,70,81,118,120,127,128]; environmental sensors [10,25,81,82,[116][117][118]123,[127][128][129][130][131][132]; temperature sensors [116,118,120,123,125,[131][132][133]; humidity sensors…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…On the other hand, the comfort cost, which is induced when the inhabitant have to modify the decision made by the system. Although this project showed promising results, it seems to be no longer active but has given rise to a number of researches by other groups [60,23] which showed that RL allows some flexibility that traditional machine learning paradigms do not. Nevertheless, if RL is particularly suitable for restricted environment (with a few possible states and actions), it poorly scales to large real cases sets.…”
Section: Related Workmentioning
confidence: 99%
“…In previous work, semisupervised learning and Markov-based models were used to generate adaptive and personalized decisions in multi-users environments [11], [12]. In this work, we consider that users through their reactions and feedback (implicit or explicit) are an important source of information on how to achieve tasks in an adaptive and personalized way (time to give medicine, path recommendation, etc.)…”
Section: Human Activity Understanding and Compliant Operationmentioning
confidence: 99%